The Effect of Reward and Competency on Employee Performance with Punishment as an Intervening Variable at the Bank Indonesia Representative Office in North Sumatra Province - Ahmad Lufthi Al Riza Siregar; Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
Companies are in dire need of competent and qualified human resources, especially in this era of globalization. All business organizations must be ready to adapt and strengthen themselves in order to compete so that they can answer all challenges in the future. Human resources in this case are employees who always play an active and dominant role in every organizational activity because humans are planners, actors and determinants of the realization of goals. This study aims to see the Effect of Reward and Competency on Employee Performance with Punishment as an Intervening Variable at the Bank Indonesia Representative Office in North Sumatra Province. The results of this study are as follows: Competence has a positive and insignificant effect on Employee Performance with the original sample value of 0.127 and p values of 0.210. Competence had a positive and significant effect on Punsihment with the original sample value of 0.433 and p values of 0.000. Punishment had a positive and significant effect on employee performance with the original sample value of 0.601 and p values of 0.002. Rewards had a positive and insignificant effect on employee performance with an original sample value of 0.158 and p values of 0.216. Reward had a positive and significant effect on Punishment with the original sample value of 0.541 and p values of 0.000. Competence has a positive and significant effect on Employee Performance through Punishment with an original sample value of 0.260 and p values of 0.006. Reward has a positive and significant effect on Employee Performance through Punishment with an original sample value of 0.325 and p values of 0.006.